Drug-prescribing pattern in chronic kidney disease patients on maintenance haemodialysis and audit of cardiovascular complications in them: Pilot study from a tertiary care hospital - Vikram Raja (Hamdan Medical Journal, 2020)
Introduction: The most frequent cause of morbidity in India is cardiovascular diseases (CVDs) complicating chronic kidney disease (CKD). Reports suggest that CKD patients with cardiovascular comorbidities are on multiple drugs, which could potentially lead to drug–drug interactions. This study intends to describe the prevalent trends in prescribing drugs for the haemodialysed CKD patients and attempts to explore the cardiovascular complications and the factors influencing them. Methodology: This observational study was conducted on CKD patients on haemodialysis, presenting to the Dialysis Centre of Father Muller Medical College, Mangalore, Karnataka, India. The study recruited a total of 107 patients from whom data were collected at the first visit and at the end of 6 months. Results: Out of the 107 patients on haemodialysis, 38 cases of cardiovascular comorbidities were noted. Hyperkalaemia was observed in 32.4%, hypokalaemia in 10.5% and normal potassium levels in 56.8% of the patients with cardiovascular comorbidities. Hyperphosphataemia was observed in 65.6%, hypophosphatemia in 0.9% and normal serum phosphate in 33.3% of the patients with anaemia. Conclusions: CVDs are common in CKD patients, and concomitant anaemia and hyperglycaemia tend to complicate the management. In such a background, appropriate care has to be exercised in the treatment of CKD.